Penerapan media visual dalam upaya meningkatkan minat belajar siswakelas vii mts negeri 1 kuningan pada materi bangun datar - Juju Juariah; Zuli Nuraeni; Ricki Yuliardi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2018)
The purpose in this research is to know of student respond to medium visual action in mathematic subject studying in order to up student interest in the classroom. The research is conducted through the stage of pre-test and cycle in which the data are collected through tests and analyzed descriptively. The result of the research shows that there is a significant improvement of the students’ interest after they have been exposed with the implementation of visual media presentation. The students’ completeness of the pre-test which is 56% and the average is 73 in Cycle I has increased to 69% with the average 76. The same thing happens to Cycle II in which it increases to 74% with the average of 78. It also happens to the Cycle III in which it increases to 86% and the average is 80. The result of the questionnaire which assesses the aspect of comprehension is 91,7 %. On the other side, the result of the questionnaire which assesses the aspect of the improvement of the students’ interest is 93,5 %. The success of improving the students’ interest is also due to the school facility, the readiness of the researcher, and the condition of the students in the classroom. The result of the research is that the implementation of visual media can increase the students’ interest in learning. The advise can give are the teacher should can to motivation the student with way study diversity in the classroom though student interest to mathematic subject can up more.